Getting ready for the COVID-19 vaccine rollout. - Park, Cyn-Young; Asian Development Bank (Manila,Philippines Asian Development Bank, [2021])
Rollout of the COVID-19 vaccine around the world comes as welcome news after the devastation of the last 12+ months. Although it is unclear when and how rollout will take place in South Africa, we are still at the precipice of the new norm. Despite the unknowns, you can expect that when the vaccine does become available there will be both a sense of urgency to administer and a reluctance to receive the vaccine from patients. To ensure your medical practice is ready from the get-go, weve put together some tips for getting vaccine ready.
Keywords: Vaccination -- COVID-19.; Physicians South Africa; Medicine South Africa; COVID-19,Disease; Physicians; Electronic book